Clinical and virological predictors of hepatic flares in pregnant women with chronic hepatitis B. Issue 11 (27th November 2014) - Giles, Michelle; Visvanathan, Kumar; Lewin, Sharon; Bowden, Scott; Locarnini, Stephen; Spelman, Tim; Sasadeusz, Joe
Abstract : Background: Unique immunological changes occur during pregnancy; the impact of which, on virological and biochemical markers of hepatitis B infection is not well established. Rapid changes in the immunological profile post partum and consequent rebound of the inflammatory response may result in hepatic flares. Methods: Women with chronic hepatitis B were recruited during pregnancy into this observational study. Demographic and clinical data were collected together with virological and biochemical parameters at two time points during pregnancy (early and late) and two time points post partum (between 6 weeks and 12 weeks and at 12 months). Outcomes analysed included changes in HBV DNA, hepatitis B e antigen (HBeAg) status and flares of hepatitis. Results: One hundred and twenty-six women were recruited. Twenty-seven women out of 108 with postpartum bloods (25%) met our definition of a postpartum flare (ALT range 38–1654). Using univariate analysis HBeAg status, younger age, gravida and parity were associated with a flare. On multivariate analysis HBeAg positivity at baseline fell just outside of statistical significance in predicting a postpartum flare (p=0.051). Conclusions: 25% of women with chronic hepatitis B will demonstrate increased liver inflammation in the postpartum period. This is usually asymptomatic and resolves spontaneously. This is more likely if the woman is HBeAg-positive at baseline (2.56 times the risk), although flares also commonly occur in HBeAg-negative women.